The Implementation of the Curriculum Religious Moderation to Foster Harmony Among Students at SMA Negeri 10 Bandung City - Koko Adya Winata; Muhammad Mufid Muafii (Bulletin of Pedagogical Research, 2025)
This study aims to examine and identify the implementation of the religious moderation curriculum in fostering harmony among students at SMA Negeri 10 Bandung. Religious-based social conflicts, intolerance, and radicalism are recurring challenges that often arise due to a lack of understanding and respect for differences. To address these issues, education plays a crucial role in cultivating harmony within a pluralistic society. Students, as the next generation, hold a vital responsibility in maintaining social harmony. Their understanding of religious moderation serves as a foundation for building a more inclusive and peaceful future. The religious moderation curriculum is expected to shape students into individuals with inclusive, tolerant, and moderate religious perspectives. This research employs a descriptive qualitative method, with data collected through interviews, documentation, and observation. The findings indicate that the implementation of the religious moderation curriculum at SMA Negeri 10 Bandung is carried out through the integration of religious moderation materials, interfaith dialogue, extracurricular activities, policy and guideline formulation, and practical application within the school environment. The implementation of this curriculum has contributed to fostering student harmony, as reflected in high levels of tolerance, understanding of religious diversity, social concern and empathy across religious lines, and the absence of religious-based conflicts. Keywords: Implementation, Religious Moderation Curriculum, Student Harmony